Biochemistry - Stryer, Lubert
This text aims to cover the principles of biochemistry and to give the reader a command of biochemistry's basic concepts and language. The fourth edition includes: a presentation of recent advances in the field of biochemistry; and an updated art programme and presentation of new molecular models.